(untitled) (The Research of Medical Science Review, 2024)
Objectives: The purpose of this study was to measure the prevalence of adherence in patients suffering from tuberculosis along with co morbidities. Method: A cross sectional observational study was conducted to measure the prevalence of adherence by using Hill-Bone Medication adherence scale on 450 patients suffering from tuberculosis and other co morbidities at Tuberculosis Center, SMBBU Hospital Larkana, Sindh, Pakistan after taking informed consent. Results: In this study 74% patients were male where as only 26% were female. Majority of the patients belongs to rural areas while few belong to urban areas. Literacy wise 136 study subjects were intermediate passed while only 29 patients were primary pass. 52% study subjects were unemployed where as only 19% patients were have government job. Majority of the patients were of 49 to 58 years of age while only 43 patients were of age from 79 years and above. 6% study subjects were prescribed 05 drugs, 9% were prescribed 06 drugs, 39% were prescribed 07 drugs, 36% were prescribed 08 drugs, 12% study subjects were prescribed 09 drugs. Co morbidity wise 35% patients were suffering from TB along with hypertension, 26 % with TB plus diabetes, 14% patients with TB plus hepatitis & 25% study subjects suffering from TB along with some other diseases. Prevalence of drug adherence among study subjects was very low. Conclusion: The study concludes that the prevalence of drug adherence to anti TB & other medicines among tuberculosis patients along with co morbidities is very low.